2014
DOI: 10.1002/anie.201406040
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of High‐Order Multiple Emulsions by the Liquid–Liquid Phase Separation of Ternary Mixtures

Abstract: Multiple emulsions with an "onion" topology are useful vehicles for drug delivery, biochemical assays, and templating materials. They can be assembled by ternary liquid phase separation by microfluidics, but the control over their design is limited because the mechanism for their creation is unknown. Herein we show that phase separation occurs through self-similar cycles of mass transfer, spinodal decomposition or nucleation, and coalescence into multiple layers. Mapping out the phase diagram shows a linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 35 publications
2
106
1
Order By: Relevance
“…For example, Haase and Brujic (2014) found that the phase behavior of lipid monolayers at an oil/water interface changes with the fraction of cholesterol in the stock solution, indicating that cholesterol successfully partitions to the interface. 59 Their studies used a silicon oil which has a significantly lower viscosity than the heavy mineral oil used in our stock oil solutions. When we performed the cDICE technique using the same silicon oil, no vesicles formed, consistent with known constraints of cDICE requiring an oil with a high viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Haase and Brujic (2014) found that the phase behavior of lipid monolayers at an oil/water interface changes with the fraction of cholesterol in the stock solution, indicating that cholesterol successfully partitions to the interface. 59 Their studies used a silicon oil which has a significantly lower viscosity than the heavy mineral oil used in our stock oil solutions. When we performed the cDICE technique using the same silicon oil, no vesicles formed, consistent with known constraints of cDICE requiring an oil with a high viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Droplets for optical tweezer experiments were prepared using a glass microfluidic device [32] with a round tapered inner capillary with inner diameter 30 μm in a square outer capillary with inner edge length 50 μm. Capillaries were supplied by VitroCom.…”
Section: Microfluidicsmentioning
confidence: 99%
“…With stronger external interphase (O/W 2 ), ripening for single-cavity structures would dominate the evolution process. [34] Copyright 2012, Wiley-VCH. [28] In addition, ripening time regulated the finale morphology.…”
Section: Phase Ripening For Emulsion Evolutionmentioning
confidence: 99%
“…Subsequently, phase separations drove the solidifications of the intermediate globules for various hollow particles. [34] With the increase of the ethanol and water compositions along the bimodal line, the proportion of the resulting multishell architectures could be improved to 500%. For solvent evaporation-based method, the middle phases were normally the volatile solvent, which contained polymers or lipids.…”
Section: Phase Separation For Hollow Structuresmentioning
confidence: 99%